Lived Experiences of Pregnant Women With Cancer in South Korea: A Qualitative Study - Da Bit Lee; Hae Won Kim; Young Jin Lee; Jieun Kim (Elsevier, 2024)
Summary: Purpose: The incidence of cancer during pregnancy is increasing, presenting several challenges to the treatment of cancer in pregnant women. However, research focusing on the lived experiences of pregnant women with cancer in South Korea is limited. This study aimed to explore and describe the day-to-day lived experiences of women diagnosed with or treated for cancer during pregnancy and their husbands. Methods: The study employed a qualitative descriptive design and utilized purposive sampling to recruit participants. The participants comprised six women living in Korea diagnosed with cancer during pregnancy and one husband of a female participant. In-depth semi-structured interviews were conducted, audiotaped, and transcribed. Five of the participants agreed to a second interview, resulting in a total of 12 individual interviews. A thematic analysis was then performed. The participants' ages ranged from 31 to 40 years, and their diagnoses during pregnancy were either breast or thyroid cancer. Results: Four main themes were identified: (1) Participants faced various heart-breaking difficulties maintaining their pregnancies throughout cancer treatment; (2) Pregnant women with cancer experienced complex but responsible feelings toward their children; (3) Patients with cancer also fulfilled their roles as parents even with their own diseases; and (4) Family support had a significant impact on the pregnant women to overcome the path. Conclusions: These findings provide a comprehensive understanding of the lived experiences of being diagnosed with cancer during pregnancy. A recommended strategy is to develop a nursing education program for pregnant women with cancer to provide necessary information and support, and to help them cope positively with their situation.